Mechanistic determinants of MBNL activity. Issue 21 (12th October 2016) - Sznajder, Łukasz J.; Michalak, Michał; Taylor, Katarzyna; Cywoniuk, Piotr; Kabza, Michał; Wojtkowiak-Szlachcic, Agnieszka; Matłoka, Magdalena; Konieczny, Patryk; Sobczak, Krzysztof
Abstract: Muscleblind-like (MBNL) proteins are critical RNA processing factors in development. MBNL activity is disrupted in the neuromuscular disease myotonic dystrophy type 1 (DM1), due to the instability of a non-coding microsatellite in the DMPK gene and the expression of CUG expansion (CUG exp ) RNAs. Pathogenic interactions between MBNL and CUG exp RNA lead to the formation of nuclear complexes termed foci and prevent MBNL function in pre-mRNA processing. The existence of multiple MBNL genes, as well as multiple protein isoforms, raises the question of whether different MBNL proteins possess unique or redundant functions. To address this question, we coexpressed three MBNL paralogs in cells at equivalent levels and characterized both specific and redundant roles of these proteins in alternative splicing and RNA foci dynamics. When coexpressed in the same cells, MBNL1, MBNL2 and MBNL3 bind the same RNA motifs with different affinities. While MBNL1 demonstrated the highest splicing activity, MBNL3 showed the lowest. When forming RNA foci, MBNL1 is the most mobile paralog, while MBNL3 is rather static and the most densely packed on CUG exp RNA. Therefore, our results demonstrate that MBNL paralogs and gene-specific isoforms possess inherent functional differences, an outcome that could be enlisted to improve therapeutic strategies for DM1.